2018
DOI: 10.1002/ecs2.2197
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathways of C and N incorporation by consumers across an experimental gradient of salmon carcasses

Abstract: Abstract. Numerous studies link resource subsidies to consumers, yet manipulations of subsidy gradients are rare, limiting our ability to predict their effects. We measured natural abundance levels of the stable isotopes of carbon (d 13 C) and nitrogen (d 15 N) in consumers representing two taxonomic (invertebrates, fish) and multiple trophic groups (primary, secondary, and tertiary consumers) exposed to a gradient of Pacific salmon carcasses (0-4 kg/m 2 , eight treatment levels) in 16 experimental streams fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 85 publications
(120 reference statements)
1
1
0
Order By: Relevance
“…Wootton (2012) documented similar shifts in stream periphyton carbon signatures in response to canopy treatments of similar magnitude on the Olympic Peninsula in Washington, but this shift in carbon propagated up to the top consumer in the system-juvenile coho salmon. Kiffney et al (2018) observed responses similar to ours, where the experimental addition of salmon carcasses in western Washington streams shifted carbon and nitrogen isotope signatures of lower trophic levels, but not top predators. In contrast, McIntyre et al (2018) observed no change in stream periphyton stable isotope signatures or biomass in response to a range of riparian buffer treatments in Washington streams.…”
Section: Stable Isotopessupporting
confidence: 84%
“…Wootton (2012) documented similar shifts in stream periphyton carbon signatures in response to canopy treatments of similar magnitude on the Olympic Peninsula in Washington, but this shift in carbon propagated up to the top consumer in the system-juvenile coho salmon. Kiffney et al (2018) observed responses similar to ours, where the experimental addition of salmon carcasses in western Washington streams shifted carbon and nitrogen isotope signatures of lower trophic levels, but not top predators. In contrast, McIntyre et al (2018) observed no change in stream periphyton stable isotope signatures or biomass in response to a range of riparian buffer treatments in Washington streams.…”
Section: Stable Isotopessupporting
confidence: 84%
“…Migratory anadromous Pacific salmon are considered strongly interacting species whose presence leads to significant ecological change, including altering species composition and energy flow (Kiffney et al, 2014;Lundberg & Moberg, 2003;Soulé et al, 2003). Although the number of adult coho salmon spawning above Landsburg Dam following restoration is relatively small compared with watersheds with healthy populations (Bradford et al, 1997(Bradford et al, , 2000Kiffney, Naman, et al, 2018;Moravek et al, 2021), we observed marked changes in the summer-time salmonid assemblage including a doubling in total biomass and increasing assemblage dissimilarity. These changes were primarily due to population-level changes in juvenile coho salmon and secondarily by mountain whitefish.…”
Section: Assemblage-level Changementioning
confidence: 64%
“…The studies focused on the salmon carcasses have found that the input of carcasses can affect individuals and communities of macroinvertebrates and microbes (Chaloner et al, 2007;Verspoor et al, 2011). A considerable number of macroinvertebrates including caddisflies, mayflies, chironomids, and chloroperlids may benefit (e.g., increased growth rate and larger population biomass) from carrion subsidy via various pathways such as direct consumption of carrion tissue, grazing on microbes colonized on decaying carrion, shredding on enhanced quality of leaf-litter, feeding on small particle organic matter detached from decomposing carrion, and by preying on other invertebrates attracted by carrion (Minakawa et al, 2002;Fenoglio et al, 2005;Kiffney et al, 2018). Decaying carrion subsidy also provide nutrient-rich food resources for microbes including both fungi and bacteria, because macronutrients (e.g., N and P), micronutrients (e.g., Ca and K), fats, and proteins leached from carcasses can stimulate the growth of microbes (Wipfli et al, 1998;Fenoglio et al, 2010;Currier et al, 2020).…”
Section: Introductionmentioning
confidence: 99%